Methods of teaching parallel programming methods in higher education - Ergashev, Nuriddin (E-Library Karshi EEI, 2023)
“Methods of teaching parallel programming methods in higher education”. Actual problems of modern science, education and training. Khorezm, October, 2021-10/1. ISSN 2181-9750; 99-103 p. http://khorezmscienee.uz.